Three different immunogen preparation strategies for production of CD4 monoclonal antibodies - Supansa Pata (2018)
Monoclonal antibodies (MAb) specific to the protein of interest can be achieved following the classical hybridoma technique. However, obtaining a desired MAb is not always straightforward. The intrinsic quality of immunogen is one of the critical success factors. In this study, three sources of immunogens were compared for CD4 MAb production. CD4 proteins were isolated by immunoprecipitation and the CD4 immunoprecipitated (CD4-IP) beads were used as an immunogen. Recombinant CD4 protein-biotin carboxyl carrier protein (BCCP) fusion proteins (CD4-BCCP) were produced in Escherichia coli, isolated by streptavidin-coated beads, and the CD4-BCCP beads were used as an immunogen. CD4 expressing COS (CD4-COS) cells were generated, enriched by immunosorting, and used as an immunogen. After three immunizations, anti-CD4 antibodies could be observed in all immunized mice. The CD4 MAbs that were generated from CD4-IP bead and CD4-COS cell immunizations reacted with both CD4 expressed on transfected COS cells and lymphocytes. These MAbs could be used for immunoprecipitation of CD4 molecules from lymphocyte lysate and for enumerating CD4+ lymphocytes by flow cytometry. In contrast, the MAb generated from CD4-BCCP bead immunization reacted only with recombinant CD4-BCCP proteins but not with native CD4 expressed on CD4+ lymphocytes. Our results indicate that the proposed methods can facilitate the production of desired MAbs where the purified protein antigens are not available or difficult to prepare, but either the encoding cDNA or specific MAb is available. © 2009, Mary Ann Liebert, Inc.